Thoughtful Accompaniment in Life's Final Stages: Philosophical Practice as a Complement to Ethics Consultation - Schuchter, Patrick (Bioethics, 2026)
This paper argues that philosophical practice can complement existing medical ethics structures by offering a publicly accessible space for discourse and negotiation of basic concepts that are relevant to ethical decision making. The potential of collaboration becomes particularly evident by the example of assisted dying: it raises a wide range of philosophical questions which, however, tend to remain unarticulated where there is urgency for action and focus on ethical dilemma. In this paper, we first provide an analysis of the neglect of profound questions in ethics consultation and why these need to be considered and negotiated within a broader socio-philosophical framework and place. These reflections are grounded in conceptual approaches informed by Immanuel Kant, Charles Taylor, and the tradition of Hellenistic philosophy as interpreted by Pierre Hadot. These frameworks are not presented as final answers, but as productive starting points and historically significant philosophical thought figures for engaging with the complex philosophical dimensions of assisted suicide. Then, we draw upon insights from an ongoing research project on philosophical practice in palliative care and hospice work. Interim results indicate that people experience a need for a kind of dialogue that gives such philosophical considerations a space and a person who is capable of facilitating it. Synthesizing theoretical-philosophical and empirical insights, the paper provides an outlook for fruitful collaboration amongst medical ethics structures and philosophical practice.